Urea treatment of maize stover for dairy cattle - Methu, J.N.; Owen, E.; Abate, A.; Tanner, J.C.; Scarr, M.J. (British Society of Animal Science, 1998)
Maize stover is the most abundant crop residue in Kenya (Methu et al., 1996). Like other cereal crop residues, maize stover is characterised by low digestibility and low crude protein. Use of ammonia to upgrade barley and wheat straw is practised in temperate countries, but in the tropics, treatment with urea to generate ammonia has been the method advocated for crop residues such as rice straw (Schiere and Ibrahim, 1989). There is need to develop information concerning treatment of maize stover for countries where maize stover is the most common crop residue. The aim of the work Reported here was to develop such information and to investigate the performance of dairy cattle fed urea treated maize stover. Chopping of maize stover is often practised in Kenya, but there is no documented information on whether this is worthwhile. Therefore the effect of urea treatment and chopping were investigated.